2020
DOI: 10.1634/theoncologist.2020-0086
|View full text |Cite
|
Sign up to set email alerts
|

Role of Surgery and Perioperative Therapy in Older Patients with Resectable Pancreatic Ductal Adenocarcinoma

Abstract: Background It is unclear whether results from recent trials of resectable pancreatic ductal adenocarcinoma (PDAC) are generalizable to older patients, who are underrepresented. We aimed to evaluate outcomes of surgery and of neoadjuvant and adjuvant therapy in older patients with resectable PDAC. Patients and Methods We included patients aged ≥65 years with upfront resectable PDAC from a prospectively maintained pancreatic cancer registry from 2007 to 2016. Patients were stratified into ages 65–75 and 75+ year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…In contrast, for patients between the ages of 65 and 75 years, NAT was associated with a similar mOS to adjuvant therapy (27.8 vs 26.8 months), and the survival benefit was very limited. [75] Cerullo et al [44] found that the estimates of OS at 1, 2, and 3 years were lower in patients who received NAT.…”
Section: Survivalmentioning
confidence: 99%
“…In contrast, for patients between the ages of 65 and 75 years, NAT was associated with a similar mOS to adjuvant therapy (27.8 vs 26.8 months), and the survival benefit was very limited. [75] Cerullo et al [44] found that the estimates of OS at 1, 2, and 3 years were lower in patients who received NAT.…”
Section: Survivalmentioning
confidence: 99%
“…Treatment decisions are more complex because of the scarcity of data from large randomised studies in older patients and the heterogeneity of this population concerning functional status, comorbidity and polypharmacy. Not age, but comorbidity, life expectancy, and patient preferences should be decisive factors when offering treatment; evidence suggests that older patients who receive treatment have improved survival outcomes (see geriatric oncology section in the extended MDT) [60]. • Some studies indicate that people with low socioeconomic status (SES) are less likely to receive surgery, chemotherapy and radiotherapy, and have higher mortality rates that those with higher SES.…”
Section: Inequalitiesmentioning
confidence: 99%
“…13,14 Several reports have confirmed the safety of pancreatic resection in elderly patients, with acceptable postoperative complication rates. [15][16][17] Similarly, administration of adjuvant chemotherapy is also considered feasible in high-performance status elderly patients. 18 That said, the safety and feasibility of delivering NAT, followed by surgical resection in the elderly remains unknown.…”
mentioning
confidence: 99%
“…Thus, aggressive management of PDAC has become feasible and acceptable, including for elderly patients 13,14 . Several reports have confirmed the safety of pancreatic resection in elderly patients, with acceptable postoperative complication rates 15–17 . Similarly, administration of adjuvant chemotherapy is also considered feasible in high-performance status elderly patients 18 .…”
mentioning
confidence: 99%